Changes in temporal sensory profile, liking, satiety, and postconsumption attributes of yogurt with natural sweeteners. Issue 7 (16th June 2022) - Chadha, Diksha; Hamid, Nazimah; Kantono, Kevin; Marsan, Manon
Abstract : Abstract: Sweetened yogurts can contain between 10 and 13% added sugar. However, studies have shown that sugar reduction or replacement can influence yogurt quality. The main objective of this research was to investigate the effects of yogurt with added natural sweeteners on temporal sensory profile, liking, satiety and postconsumption measures. Yogurt samples were prepared with iso‐sweet concentrations of sucrose (9 g/100 g of plain yogurt) using xylitol (10 g/100 g), stevia (0.15 g/100 g), and monk fruit (0.15 g/100 g). Fifty panelists evaluated the temporal sensory profile of these yogurts using multiple‐intake temporal dominance of sensations (TDS), and overall liking for each intake. In addition, satiety (hunger, thirst, and fullness) and other postconsumption attributes (healthiness, satisfaction, and purchase intent) were determined. The temporal profile of yogurt sweetened with xylitol was similar to yogurt sweetened with sucrose without any onset of negative sensory characteristics at any point in intake. Yogurt sweetened with stevia had a high dominance duration for astringency. Moreover, yogurt sweetened with monk fruit showed increased dominance of attributes bitter and astringent from the first to third intake. In terms of liking, yogurt containing xylitol was scored the highest followed by stevia and monkfruit. Sweet was a positive temporal driver of liking in yogurt sweetened with monk fruit. However, mouthcoating, sweet, and sour decreased liking in yogurt sweetened with sucrose, xylitol, and stevia respectively. In terms of perceived healthiness, satisfaction and purchase intent, yogurt sweetened with sucrose scored the highest followed by xylitol. Consumption of yogurt sweetened with xylitol, stevia, or monk fruit significantly decreased hunger compared to yogurt sweetened with sucrose. Practical Application: The current findings will play an important role for the dairy industry in understanding how sugar replacement with natural sweeteners in yogurt can influence its sensory perception and postconsumption behavior.